The role of hedonic consumption tendency mediate the effect of fashion involvement on impulsive buying - Sari, Made Diah Kencana; Yasa, Ni Nyoman Kerti (International research journal of management, IT and social sciences, 2021)
This study aims to examine the effect of fashion involvement on impulsive buying mediated by hedonic consumption tendencies. The population in this study are consumers of ZARA fashion products who have made unplanned purchases in Kuta, whose numbers cannot be identified (infinite). The number of respondents involved in this study was 100 respondents. The data in this study were obtained from the results of filling out a questionnaire. Further research data were analyzed using the Partial Least Square (PLS) analysis technique with the help of the Smart PLs program. Based on the results of the PLS analysis, the results show that (1) the involvement of fashion has a positive and significant effect on impulsive buying of Zara’s fashion products, (2) The involvement of fashion has a positive and significant effect on the tendency of hedonic consumption, (3) The tendency of hedonic consumption has a positive and significant effect on purchases impulsive fashion products Zara and (4) the hedonic consumption tendency can mediate the influence of fashion involvement on impulsive buying.